Organoleptic Quality of Chicken Sausage with Different Brands in Kediri City - Anif Mukaromah Wati; Siti Azizah (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2023)
Sausage is one type of processed chicken meat wrapped in a sleeve. Chicken sausage is a food that is in great demand by modern society, especially during the Covid-19 pandemic season because it is practical, affordable, cheap, durable, and can be found anywhere. Based on its population, the Kediri city is the third largest city in East Java. During the pandemic and after the pandemic, chicken sausage was one of the products that experienced an increase. The purpose of this study was to examine the organoleptic quality of chicken sausages in the Kediri city. The research was conducted in October-December 2020 at Universitas Brawijaya Kediri on five different samples chicken sausage. The composition of the sample was recorded and the organoleptic quality was analyzed by 50 semi-trained panelists. The results of the organoleptic test showed that the different types of chicken sausage had highly significant difference (p<0.01) on the color, texture, aroma, chicken sausage taste, juiciness, ease of biting, ease of chewing, and hedonic chicken scale. Chicken sausage that has the best organoleptic score is sausage brand number 2 with the highest score on texture, aroma, chicken sausage taste, juiciness, ease of biting, ease of chewing, and hedonic chicken sausage, while the assessment of color, panelists prefer brand number 3. Â The conclusion of this study is brand 2 which is a sausage brand â€œBernardiâ€ has the best acceptance by consumers because this sausage is made from premium ingredients and paprika oleoresin with a natural taste.